Fabrication of arrays of sub-20-nm silica walls via photolithography and solution-based molecular coating - Fujikawa, Shigenori (Langmuir : the ACS journal of surfaces and colloids, 2006)
We report herein fabrication of arrays of sub-20-nm silica walls via photolithography and the surface sol-gel process. A photolithographically fabricated line template on a silicon wafer was coated with a silica nanolayer using the surface sol-gel process, and then the topmost portion of the silica layer and the template were successively removed using CHF(3) and oxygen plasma, respectively, leaving the sidewalls of the silica layers remaining on the substrate. These walls were fully self-supporting, and the thicknesses of silica wall were 6, 8, and 12 nm at 20, 30, and 60 cycles, respectively. The height/width ratio of the wall was 38 at the 30-cycle coating. This ratio is surprisingly high when compared to that of the conventional photolithography processes. Successive formation of the silica, polymer, and silica layers yielded a trilayer sidewall, and the spacer polymer layer could be selectively removed to form a doubled sidewall. Size reduction and proliferation of sub-20-nm silica wall was thus achieved. The reported method is simple and cost-efficient and opens a gateway to further miniaturization of nanostructures